Direct differentiation of tonsillar biopsy-derived stem cells to the neuronal lineage - Michal Arad; Robert A. Brown; Raju Khatri; Rodney J. Taylor; Michal Zalzman (Cellular & Molecular Biology Letters, 2021)
Abstract Background Neurological disorders are considered one of the greatest burdens to global public health and a leading cause of death. Stem cell therapies hold great promise for the cure of neurological disorders, as stem cells can serve as cell replacement, while also secreting factors to enhance endogenous tissue regeneration. Adult human multipotent stem cells (MSCs) reside on blood vessels, and therefore can be found in many tissues throughout the body, including palatine tonsils. Several studies have reported the capacity of MSCs to differentiate into, among other cell types, the neuronal lineage. However, unlike the case with embryonic stem cells, it is unclear whether MSCs can develop into mature neurons. Methods Human tonsillar MSCs (T-MSCs) were isolated from a small, 0.6-g sample, of tonsillar biopsies with high viability and yield as we recently reported. Then, these cells were differentiated by a rapid, multi-stage procedure, into committed, post-mitotic, neuron-like cells using defined conditions. Results Here we describe for the first time the derivation and differentiation of tonsillar biopsy-derived MSCs (T-MSCs), by a rapid, multi-step protocol, into post-mitotic, neuron-like cells using defined conditions without genetic manipulation. We characterized our T-MSC-derived neuronal cells and demonstrate their robust differentiation in vitro. Conclusions Our procedure leads to a rapid neuronal lineage commitment and loss of stemness markers, as early as three days following neurogenic differentiation. Our studies identify biopsy-derived T-MSCs as a potential source for generating neuron-like cells which may have potential use for in vitro modeling of neurodegenerative diseases or cell replacement therapies.